Perilaku Masyarakat Terhadap Pasal 29 UUD 1945 Atas Perbuatan Pembubaran Ibadah Secara Paksa Berdasarkan Perspektif Hukum Pidana - Pratiwi Br. Tambun, Dina; Gabriel Siahaan, Parlaungan (UNES Law Review, 2024)
This research aims to find out and analyze the extent to which people's behavior towards legal rules protects the law in implementing a life that has high religious tolerance. This research is normative-empirical legal research, namely research that examines the implementation or implementation of positive legal provisions (legislation) and written documents in action (factual) on each specific legal event that occurs in society. This research was carried out using interview and observation methods with informants, namely the Satia Village Community, Binjai Kota District, North Sumatra and the Binjai City Police Department, and the Binjai Religious Harmony Forum (FKUB). Then the data analysis techniques in this research are data reduction, data presentation and drawing conclusions. The research results show that on May 19 2023, there was an incident of forced disbandment of the Mawar Sharon Church (GMS) congregation in Satia Village. Around 40-50 local residents protested the worship activity even though GMS had obtained permission from FKUB. This incident sparked strong reactions from the wider community and various organizations who condemned the forced disbandment. Based on the results of interviews with 12 respondents in Satia Village, the majority of respondents condemned this action and understood that the forced disbandment of worship violated Article 29 of the 1945 Constitution which guarantees freedom of religion. However, some people still feel uncomfortable with worship activities carried out by other religious groups in Muslim-majority environments. FKUB Binjai plays an active role in mediating and seeking peaceful solutions to overcome these disturbances. They also emphasized the importance of dialogue and mutual understanding to prevent future conflict. Overall, this research shows that although the public's understanding of religious freedom is relatively good, greater efforts are still needed from the government and related institutions to improve legal protection of religious freedom in Indonesia. More intensive education, better coordination between institutions, and increased human resources and budgets are necessary steps to achieve this goal. Apart from that, society's response to minority religious forms also needs to be improved through the involvement of various parties, including religious leaders, to change society's way of thinking.